2020
DOI: 10.1186/s12970-020-00353-w
|View full text |Cite
|
Sign up to set email alerts
|

The athletic gut microbiota

Abstract: The microorganisms in the gastrointestinal tract play a significant role in nutrient uptake, vitamin synthesis, energy harvest, inflammatory modulation, and host immune response, collectively contributing to human health. Important factors such as age, birth method, antibiotic use, and diet have been established as formative factors that shape the gut microbiota. Yet, less described is the role that exercise plays, particularly how associated factors and stressors, such as sport/exercise-specific diet, environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
203
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(216 citation statements)
references
References 241 publications
(349 reference statements)
0
203
0
13
Order By: Relevance
“…Commonly used probiotic strains for the application of exercise include Lactobacillus , Bifidobacterium , and Bacillus genera, however, new microbiome research and technological advances are identifying potential next-generation probiotic candidates [ 4 ]. In the context of exercise, and especially athletes, the present body of literature suggests their microbiota has several key differences in comparison with other populations, likely driven, in part, by exercise and diet [ 5 ▪ ]. These characteristics may influence the effects of probiotics on the resident microbiome and host physiology, as well as consideration for probiotic application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used probiotic strains for the application of exercise include Lactobacillus , Bifidobacterium , and Bacillus genera, however, new microbiome research and technological advances are identifying potential next-generation probiotic candidates [ 4 ]. In the context of exercise, and especially athletes, the present body of literature suggests their microbiota has several key differences in comparison with other populations, likely driven, in part, by exercise and diet [ 5 ▪ ]. These characteristics may influence the effects of probiotics on the resident microbiome and host physiology, as well as consideration for probiotic application.…”
Section: Introductionmentioning
confidence: 99%
“…However, the recent positive findings noted above are promising and investigators are encouraged to continue this line of research for both macro and micronutrients. It may be that the exercise associated gut microbiota may be more receptive to improved nutrient utilization as it appears to possess a functional capacity that is primed for tissue repair and a greater ability to harness energy from the diet with increased capacity for carbohydrate, cell structure, and nucleotide biosynthesis [ 5 ▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics studies have quantitively illustrated how stress can reduce intestinal barrier integrity, altering gut microbiota composition, which in turn modulates immunoregulatory responses in the host (9,40,41). A compromised gut microbiota profile introduces disruption in the uptake of fluids, electrolytes, and vital nutrients, exerting negative impacts on exercise performance and recovery (42)(43)(44). Host-gut microbiota interactions are also implicated in the nervous system control of glucose, impacting another aspect of host metabolic efficiency (45).…”
Section: Downloaded Frommentioning
confidence: 99%
“…The gut microbiome is highly dynamic and correlated with multiple factors including diet, genetic makeup, stress, socioeconomic status, interactions between social and physical environments (42), and exercise (43). It fluctuates over time (13) and varies biogeographically across different sections of the gut (14).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Recent research has revealed that the gut microbiota impacts the host physiology and human health [2]. Indeed, the data obtained on earth argue to preserve an optimized gut microbiota composition, as its disruption/deregulation of these bacteria communities referred to as dysbiosis, is associated with health disorders [3] and/or altered physical performance [4][5][6][7][8]. As a modulator of the immune system, the gut microbiota contributes to intestinal homeostasis and integrity (permeability and in ammation) and exerts a nutritional role via its bacteria-derived metabolites [4].…”
Section: Introductionmentioning
confidence: 99%